2022
DOI: 10.1246/cl.220017
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid-catalyzed Decarboxylative Cyanation of Cyclic Enol Carbonates — Access to Multi-substituted β-Ketonitriles —

Abstract: A Lewis acid-catalyzed decarboxylative substitution reaction of cyclic enol carbonates with a cyanation reagent was developed to give β-ketonitriles in good yield. It is proposed that the reaction proceeds through an oxyallyl cation intermediate or its equivalent. Interestingly, cyanation selectively took place at the more hindered site of the intermediate to afford a multi-substituted β-ketonitrile. This regioselectivity was observed by the cyanation of a wide range of substrates and is discussed in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In fact, we recently reported that the decarboxylative allylation of cyclic enol carbonates was triggered by an excess amount of zirconium tetrachloride in the presence of an allyl silane, resulting in the formation of homoallylic ketones . More recently, we achieved the synthesis of β-ketonitriles on the basis of the trityl cation-catalyzed decarboxylative cyanation reaction of cyclic enol carbonates . In order to investigate applications of the decarboxylative intermolecular bond formation reaction using cyclic enol carbonates, we aimed to develop an intermolecular carbon–carbon bond formation reaction with other carbon nucleophiles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we recently reported that the decarboxylative allylation of cyclic enol carbonates was triggered by an excess amount of zirconium tetrachloride in the presence of an allyl silane, resulting in the formation of homoallylic ketones . More recently, we achieved the synthesis of β-ketonitriles on the basis of the trityl cation-catalyzed decarboxylative cyanation reaction of cyclic enol carbonates . In order to investigate applications of the decarboxylative intermolecular bond formation reaction using cyclic enol carbonates, we aimed to develop an intermolecular carbon–carbon bond formation reaction with other carbon nucleophiles.…”
mentioning
confidence: 99%
“…Recently, the Lewis acid-catalyzed decarboxylative transformations of cyclic enol carbonates have been reported by our group (Scheme ). In the proposed reaction mechanism, the decarboxylation of the cyclic enol carbonate is promoted by a Lewis acid and results in the formation of an oxyallyl cation intermediate or its equivalent. The utility of the oxyallyl cation intermediate was demonstrated by the intramolecular carbon–carbon bond formation reactions, such as the Nazarov cyclization and the homo-Nazarov cyclization, and intramolecular cyclization involving nucleophilic halogenation .…”
mentioning
confidence: 99%
“… A cyclohexenone was also constructed by the decarboxylative homo-Nazarov cyclization, and a functionalized cycloheptanone was synthesized by intramolecular cyclization involving nucleophilic halogenation . More recently, the decarboxylative transformation was further extended to intermolecular carbon–carbon bond forming reactions, such as allylation and cyanation, coupling with silyl enol ethers . For our proposed reaction mechanism, an oxyallyl cation, generated by the decarboxylation of the cyclic enol carbonates, is the key intermediate, and we envisioned that the oxyallyl cation intermediate could be applied to other ring-closing transformations.…”
mentioning
confidence: 99%
“…The Lewis acid-catalyzed decarboxylative transformation of cyclic enol carbonates has recently been developed by our group. 6,7 In our proposed reaction mechanism, the decarboxylation of the cyclic enol carbonate is initiated by a Lewis acid, resulting in the formation of an oxyallyl cation intermediate or its equivalent (Scheme 2). The intermediate could be utilized for intramolecular carbon–carbon bond formation reactions, such as the Nazarov cyclization.…”
mentioning
confidence: 99%